2023
DOI: 10.1017/s1352465822000273
|View full text |Cite
|
Sign up to set email alerts
|

CBT for difficult-to-treat depression: self-regulation model

Abstract: Background: Cognitive behavioural therapy (CBT) is an effective treatment for depression but a significant minority of clients do not complete therapy, do not respond to it, or subsequently relapse. Non-responders, and those at risk of relapse, are more likely to have adverse childhood experiences, early-onset depression, co-morbidities, interpersonal problems and heightened risk. This is a heterogeneous group of clients who are currently difficult to treat. Aim: The aim was to develop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…A coloured dot indicates that the relevant component was delivered in that session. The components were derived from the self-regulation model of depression (Barton et al, 2023), delivered in the amount and sequence indicated by the emerging case formulation, not a pre-set protocol. More than one component could be delivered in any particular session.…”
Section: Process Of Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A coloured dot indicates that the relevant component was delivered in that session. The components were derived from the self-regulation model of depression (Barton et al, 2023), delivered in the amount and sequence indicated by the emerging case formulation, not a pre-set protocol. More than one component could be delivered in any particular session.…”
Section: Process Of Therapymentioning
confidence: 99%
“…He requested further therapy to address the conflictual relationship with his father, and this article describes a subsequent long-term course of CBT that used a trauma focus to address this. In David's case, an individualised formulation was developed using the self-regulation model of depression (Barton and Armstrong, 2019;Barton et al, 2022;Barton et al, 2023). This sought to explain how historical trauma contributed to the triggering and maintenance of David's depressive episodes, through its impact on his self-identity.…”
mentioning
confidence: 99%
“…In CBT terms, depression initially forged ahead with the development of Beck’s cognitive therapy, but subsequently lagged behind possibly because of lags in theory development. Stephen Barton’s article (Barton et al ., 2023) considers CBT for difficult-to-treat depression and provides a theoretical context. Theory is also a major feature of the article from Mark Freeston (Freeston, 2023) considering how best to apply theory to generalised anxiety disorder.…”
mentioning
confidence: 99%